BUDAYA MUSIK TRADISIONAL RAPAI DABOH SEBAGAI KEARIFAN LOKAL PULO SUNONG KECAMATAN TANGSE, KABUPATEN PIDIE - Hikmal, Yusran; Saputri, Yuni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2025)
This study aims to explore the symbolic meaning, cultural values, and social functions of Rapai Daboh, a traditional performance art that embodies the local wisdom of the Pulo Sunong community in Tangse District, Pidie Regency. Rapai Daboh combines rhythmic drumming, religious chants, and physical rituals that reflect Islamic teachings, communal solidarity, moral values, and aesthetic traditions. Employing a qualitative approach, the research utilized observation, documentation, literature study, and in-depth interviews. The findings reveal that Rapai Daboh serves not only as a form of entertainment but also as a medium for Islamic preaching, cultural preservation, and social identity reinforcement. These values are maintained and passed down through consistent performances, regular rehearsals, and strong communal support. Rapai Daboh stands as a symbol of cultural resilience in the face of modernization and remains a living tradition within Acehnese societyKeywords: Rapai Daboh, Local Wisdom, Traditional Acehnese Music, Cultural Preservation